Numerical and experimental analysis of the flat plate solar water heater systems' thermal performance. Issue 2 (30th September 2022) - Freegah, Basim
Abstract: In this paper, improving the thermal performance of flat plate solar water heater systems by inserting different tube configurations inside the riser pipes has been numerically and experimentally studied. This study is focused on increasing the moving of energy from riser pipes to the operating fluid within the riser pipes. To achieve that, the diameter of the riser pipes was increased along with the insertion of different tube configurations within them, namely, smooth, helical, and wavy tubes, keeping the same amount of the operating liquid. A comparison was performed to determine the best in terms of coefficient of heat transfer of the operating liquid, mass flow rate of the operating liquid, pressure drop, and water temperature in the storage tank, as a thermal performance indication of the system under study. The findings show the model consisting of a straight tube inside the riser pipe provides the best thermal performance. In terms of thermal performance, the straight model outperforms the conventional model by 12.3%. An experimental and numerical comparison between the optimum model (straight model) was conducted. The study proves that the average difference between numerical results and experimental findings is 7.2%.